Epidemiologic Profile and Clinical Outcomes of Patients with Pheochromocytoma at the University of the Philippines - Philippine General Hospital (UP-PGH) - Hernandez, Edrome; Jimeno, Cecilia; Paz-Pacheco, Elizabeth (Journal of the ASEAN Federation of Endocrine Societies, 2024)
Objective. This study aims to describe the epidemiologic profile and determine the clinical outcomes of patients with pheochromocytoma at the University of the Philippines Philippine General Hospital (UP-PGH). Methodology. We reviewed the medical records of 30 patients with histopathology-proven, clinical, and biochemical diagnosis of pheochromocytoma. Demographic, clinical characteristics, and clinical outcomes were collected for each patient. Results. The median age at diagnosis of pheochromocytoma was 37.5 years (IQR 28-55) and the most common metabolic comorbidities were glucose intolerance (60%) and hypertriglyceridemia (23.3%). Majority of the patients were hypertensive (90%). Two third of the patients presented with classic features of pheochromocytoma while the remaining third presented as adrenal incidentaloma. Recurrence was found in 17% of subjects, who were significantly younger (25 years vs 46.5 years P = 0.0229), and had higher rates of bilateral pheochromocytoma (0 vs 75%), p = 0.002). Metastatic pheochromocytoma was found in 10% of the subjects. Conclusion. Our study demonstrated that patients with pheochromocytoma in our setting exhibit great variability in terms of clinical behavior. Although majority of the patients presented with symptoms related to catecholamine excess, almost one-third of the patients were only incidentally discovered. Incidence of pheochromocytoma recurrence and metastasis in our setting are comparable with current available foreign studies.